Short Course versus Standard Course Antibiotic Treatment for Neonatal Sepsis (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Neonatal sepsis remains an important cause of morbidity and mortality and often requires prompt empiric treatment. However, only a minority of babies who receive antibiotics for suspected sepsis have an infection. Antimicrobial exposure in infancy has important short-term and long-term consequences. There is no consensus regarding empirical antimicrobial regimens.Objective: To compare efficacy and benefits of short course (5 days) over the standard course (7 days) antibiotic treatment for neonatal sepsis.Materials and Methods: The study was a randomized controlled trial done in the neonatal ward in a tertiary level hospital comprising total 100 term neonates equally divided in to two groups by randomization where Group-I (5 days antibiotic therapy) was compared against Group-II (7 days antibiotic therapy) in clinical recovery, hospital stay, morbidity such as seizure, developmental delay etc and mortality.Results: The study results showed that both the Group-I and Group-II were comparable in baseline clinical data and predisposing factors; however, there was no significant difference between the two groups in clinical features e.g. hypotonia (24% vs 26%, p>0.05), poor primitive reflexes (46% vs 52%, p>0.05), temperature instability (34% vs 28%, p>0.05), feeding intolerance (16% vs 14%, p>0.05), apnea / respiratory distress (28% vs 34%, p>0.05) and in clinical outcome e.g. hospital stay (5.24±0.78 vs 7.86±0.42, p>0.05), recovery (86% vs 90%, p>0.05), death (14% vs 10%, p>0.05), seizure disorder (8% vs 6%, p>0.05) and developmental delay (6% vs 4%, p>0.05).Conclusion: This study showed that there was no significant difference between the study groups in clinical outcome, however, short course antibiotic (5 days) is equally effective but economically more beneficial to standard course antibiotic (7 days) therapy for neonatal sepsis.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 124-127